Pengaruh CR dan DER Terhadap ROA Pada Perusahaan Subsektor Industri Tambang Emas Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Muhamad Firmansyah; Henny Armaniah (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the decreasing production of gold mines every year, which will also affect the company's profitability. As for the methods used to measure the level of profitability of a company, one of them is by using return on assets. The level of profitability is also influenced by several other factors, including the current ratio and debt to equity ratio. The purpose of this research is to determine and analyze the influence of the Current Ratio and Debt To Equity Ratio on Return On Assets, both partially and simultaneously. This research uses descriptive quantitative methods. Researchers collected, classified and analyzed sample data using purposive sampling techniques. With 6 company samples consisting of 30 data selected and analyzed using the IBM SPSS version 27 program. The results of research and partial hypothesis testing. Current Ratio has no significant effect on Return On Assets with a value of tcount 1.228 < ttable 2.052. Debt To Equity Ratio has a significant effect on Return On Assets with a value of tcount 2.725 > ttable 2.052. The results of research and hypothesis testing with a value of Fcount 4.020 > Ftable 3.369 from the Current Ratio and Debt To Equity Ratio simultaneously have a significant effect on the Return On Assets of gold mining industry subsector companies listed on the Indonesia Stock Exchange for the 2018-2022 period.